The Effect of Tax Uncertainty, Stock Market Liquidity, Earnings Management on Indonesian Firm's Investment - Kurniawan, Validita; Firmansyah, Amrie (SBM ITB, 2019)
Abstract. The prosperous economy of the country is closely related to the role of investment, especially private sector investment. This study aims to examine the effect of tax uncertainty, stock market liquidity, and earnings management on firm's investment in Indonesia. Through an associative quantitative approach, this study analyzed firms listed on the Indonesia Stock Exchange from 2014 up to 2016 which is examined using the fixed effect model of panel data. The results of this study suggest that tax uncertainty and stock market liquidity are negatively associated with firm's investment. Meanwhile, earnings management is not associated with firm's investment.Keywords: Firm's investment, tax uncertainty, stock market liquidity, earnings management.Abstrak. Perekonomian suatu negara tidak terlepas dari peran investasi, khususnya investasi sektor swasta. Penelitian ini bertujuan untuk menguji pengaruh ketidakpastian pajak, likuiditas pasar saham, dan manajemen laba terhadap investasi perusahaan di Indonesia. Melalui pendekatan asosiatif kuantitatif, penelitian ini menganalisis perusahaan yang terdaftar pada Bursa Efek Indonesia pada tahun 2014 hingga 2016 yang diuji menggunakan model fixed effect dari data panel. Hasil penelitian ini menunjukkan bahwa ketidakpastian pajak dan likuiditas pasar saham memiliki pengaruh negatif terhadap investasi perusahaan. Sementara itu, manajemen laba tidak mempengaruhi investasi perusahaan.Kata kunci: Investasi perusahaan, ketidakpastian pajak, likuiditas pasar saham, manajemen laba